Aspects Regarding the Modelling and Design of 3D-printed Bending Soft Pneumatic Actuators. Issue 1 (1st November 2022) - Rad, C; Hancu, O; Lapusan, C
Abstract : Soft robotics has the potential to revolutionize our society and industries due to its increased adaptability and soft interaction with environment. In this context, the paper presents the results of finite element modelling and design of two 3D-printed bending soft pneumatic actuators made from NinjaFlex ® flexible filament. Geometrical parameters of the actuators were chosen based on the recommendations from the literature and NinjaFlex ® material elastic properties were modelled using Ogden hyperelastic model. The simulation was implemented in ANSYS® Workbench software and both designs were compared and analysed in terms of bending angle performance and equivalent (von-Mises) stresses for an input pressure of 0.1÷0.5 MPa with an increment of 0.1 MPa. The obtained simulation results can be used as a design guideline for 3D-printed bending soft pneumatic actuators made from flexible thermoplastic polyurethanes.